Perancangan Sistem Informasi Penjualan Dan Bembelian Serta Pengendalian Stok Barang Pada Toko Batik Kusumawardani Solo - Yamotiwode Abraham Badii; Ratna Herawati (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Toko Batik Kusumawardani system transactions engaged in sales and booking special batik clothes and other clothes through purchase or booking directly on the spot. In the section on data management sales of goods in the Toko Batik Kusumawardani had previously been using a manual recording system. However the use of this system is insufficient. In the process of ordering goods are still done manually by using the notes. Hence the need for the sale of goods transaction system at the Toko Batik Solo Kusumawardani already computerized. The method of the approach system used on this information system using the method waterfall. The design of the system used on this information system using Vb.Net, UML, MySql database , and CrystalReport. Proceeds from the sale of this system is to make it easier for the admin to manage data items, sales reports and print notes customers. With the application of the system of sale of goods in the Toko Batik Solo Kusumawardani, existence of the negligence, may reduce buildup of documents, and sales reports are not accurate and not on time.Keywords: System sales of goods the Toko Batik Kusumawardani, Vb.Net, MySql, the CrystalReport.